Multi-Functional Alginate Lyase AlgVR7 from Vibrio rumoiensis: Structural Insights and Catalytic Mechanisms - Zhe Huang; Shuai Liang; Wulong Jiang; Li Wang; Yuan Wang; Hua Wang; Lianshun Wang; Yuting Cong; Yanan Lu; Guojun Yang (Marine Drugs)
In this study, we identified AlgVR7, a novel bifunctional alginate lyase from Vibrio rumoiensis and characterized its biochemical properties and substrate specificity. Sequence alignment analysis inferred the key residues K267, H162, N86, E189, and T244 for AlgVR7 catalysis, and it is derived from the PL7 family; exhibited high activity towards sodium alginate, polyM (PM), and polyG (PG); and can also degrade polygalacturonic acid (PGA) efficiently, with the highest affinity and catalytic efficiency for the MG block of the substrate. The optimal temperature and pH for AlgVR7 were determined to be 40 °C and pH 8, respectively. The enzyme activity of AlgVR7 was maximum at 40 °C, 40% of the enzyme activity was retained after incubation at 60 °C for 60 min, and enzyme activity was still present after 60 min incubation. AlgVR7 activity was stimulated by 100 Mm NaCl, indicating a halophilic nature and suitability for marine environments. Degradation products analyzed using ESI-MS revealed that the enzyme primarily produced trisaccharides and tetrasaccharides. At 40 °C and pH 8.0, its Km values for sodium alginate, PM, and PG were 16.67 μmol, 13.12 μmol, and 22.86 μmol, respectively. Structural analysis and molecular docking studies unveiled the key catalytic residues involved in substrate recognition and interaction. Glu167 was identified as a critical residue for the PL7_5 subfamily, uniquely playing an essential role in alginate decomposition. Overall, AlgVR7 exhibits great potential as a powerful bifunctional enzyme for the efficient preparation of alginate oligosaccharides, with promising applications in biotechnology and industrial fields.